Differences in the digital home lives of young people in New Zealand - Hartnett MK (Wiley)
Digital technology is changing every aspect of life from how we communicate to the way we learn. International trends would suggest that digital access is becoming increasingly widespread in developed countries. But general trends may hide the fact that some households still do not have access to the internet for a variety of reasons. Differences in digital access and use, particularly along socio-economic lines, may be less visible but are still present. This paper reports on a two-phase study that explores home digital access and use of young people (16–17–years-old) from a range of socio-economic backgrounds across New Zealand. Phase one sought to establish what home access is available, while the second phase explores what kinds of digital technologies are used and for what purpose among a subset of young people. Results indicate that differences in digital access do exist among young people from different socio-economic backgrounds. These differences include the number of digital devices in the home, the types of devices available, and whether the device(s) are shared or individually owned. These findings are particularly important in light of the finding that these young people perceived that digital access and use at school is inadequate and lagging behind everyday use. This suggests that there is still a considerable way to go to ensure equal digital opportunities for all.
Keywords: 1099 Other Technology; 1301 Education Systems; 1303 Specialist Studies in Education